THE IMPACT OF CUSTOMER FOCUS STRATEGY ON CLIENT SATISFACTION WITH THE MEDIATING ROLE OF INNOVATION CAPABILITY IN THE IT OUTSOURCING INDUSTRY - Hidayat, Ravindra Safitra; Maulana, Panca; Muhdaliha, Eryco (Management and Leadership Study Programme, 2025)
This study aims to analyze the extent to which a customer focus strategy influences client satisfaction in the IT outsourcing industry, considering the mediating role of innovation capability. The key research question is: how does innovation capability strengthen the relationship between a customer focus strategy and client satisfaction? Through surveys and interviews with managers from IT outsourcing companies and their clients, the findings reveal that a customer focus strategy has a significant positive effect on client satisfaction. Additionally, innovation capability acts as a mediator that reinforces this relationship. The data show that companies integrating innovation into their customer service are able to enhance client loyalty and foster a more positive perception of service quality. These findings are particularly relevant in the IT industry, where accurately meeting client needs is crucial for maintaining competitive advantage. The study's implications may also be extended to other sectors, encouraging companies to make innovation an integral part of their service strategy in order to improve customer satisfaction and loyalty on an ongoing basis. Overall, this research offers new insights for practitioners and academics to optimize business strategies by emphasizing innovation, thereby contributing to the development of best practices in IT outsourcing.